Cognitive developmental foundations of cultural acquisition: children's understanding of other minds - Burdett, E (2013)
Psychological research suggests that children acquire cultural concepts through early developing cognitive mechanisms combined with specific cultural learning. An understudied area of cultural acquisition is children’s understanding of non-human minds, such as God. This thesis gives evidence that young children need not anthropomorphize non-human minds in order to understand them. Instead, children have a general “theory of mind” that is tailored through experience to accommodate the various important minds in their cultural environment. The intuitive default is toward super-attributes, making children naturally inclined or “prepared” to acquire god concepts. Four empirical studies were conducted with 75 British and 66 Israeli preschool-aged children. In Study 1, children participated in an ignorance-based theory-of-mind task and were asked to consider the mental states of human and supernatural agents. Children at all ages attributed correct knowledge to the supernatural agents and ignorance to the human agents. In Study 2, children participated in two perception-based theory-of-mind tasks and were asked to consider the perspective of two super-perceiving animals, God, and two human agents. Three-year-olds attributed knowledge to the animals and God and, by age four, children could distinguish among agents correctly. Also, by age four, children recognized that aging limits the perception of human agents but not God’s. In Study 3, children participated in a memory-based theory-of-mind task in which they were asked to consider the memory of God and differently aged agents Children at all ages responded that God would remember something that the children themselves had forgotten. By age five, children responded that a baby and granddad would have forgotten. These results propose that preschool-aged children regard individual constraints when considering mental states. Study 4 focused on children’s notions of immortality. Cultural differences were found. British children attributed immortality to God before correctly attributing mortality to human agents, and Israeli children attributed immortality to God and mortality to humans more consistently than did British children. Collectively, these studies indicate that children do not have to resort to anthropomorphism to reason about non-human agents but instead have the cognitive capacity to represent other types of minds because of early cognitive capacities. It appears that concepts vary in their degree of fit with early-developing human conceptual systems, and hence, vary in their likelihood of successful cultural transmission.